Exploring Anorectal Manometry as a Method to Study the Effect of Locally Administered Ropivacaine in Patients with Ulcerative Colitis. (17th February 2013) - Arlander, Eva; Löfberg, Robert; Törkvist, Leif; Lindforss, Ulrik
Abstract : The symptoms of distal ulcerative colitis have been related to changes in rectal sensitivity and capacity due to inflammation, altered gastrointestinal motility, and sensory perception. With the use of anorectal manometry, the function was measured in seven patients with active distal proctitis during local treatment with ropivacaine. Seven healthy subjects were studied in the same way for comparison with normal conditions. The anal resting pressure and squeezing pressure were similar in all groups. Significantly lower rectal distention volumes were required for rectal sensation, critical volume, and to induce rectal contractility in patients with active disease compared to controls. Rectal compliance was significantly reduced in patients with active and quiescent disease. The increased rectal sensitivity and contractility in patients with active colitis appear to be related to active mucosal inflammation and ulceration. The frequency and urgency of defecation and the fecal incontinence may be due to a hypersensitive, hyperactive, and poorly compliant rectum. The findings in our study indicate that the inflammatory damage to the rectal wall with poor compliance is unaffected by local anaesthetics such as ropivacaine. The symptomatic relief and reduction in clinical symptoms following treatment are not reflected in the anorectal manometric findings.